2016
DOI: 10.1109/tie.2016.2581155
|View full text |Cite
|
Sign up to set email alerts
|

Small-Signal Analysis of the Microgrid Secondary Control Considering a Communication Time Delay

Abstract: Abstract-This paper presents a small-signal analysis of an islanded microgrid composed of two or more voltage source inverters connected in parallel. The primary control of each inverter is integrated through internal current and voltage loops using PR compensators, a virtual impedance, and an external power controller based on frequency and voltage droops. The frequency restoration function is implemented at the secondary control level, which executes a consensus algorithm that consists of a load-frequency co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
0
17

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(126 citation statements)
references
References 22 publications
0
109
0
17
Order By: Relevance
“…It's important to consider how to maintain MGC stability under the conditions of the fixed delays and random delays. This is also the main obstacle to apply the hierarchical control and MAS theory to solve the practical engineering problems [192].…”
Section: A Communication Mechanism Of the Multi-agent System Inmentioning
confidence: 99%
See 1 more Smart Citation
“…It's important to consider how to maintain MGC stability under the conditions of the fixed delays and random delays. This is also the main obstacle to apply the hierarchical control and MAS theory to solve the practical engineering problems [192].…”
Section: A Communication Mechanism Of the Multi-agent System Inmentioning
confidence: 99%
“…7 (c), can be used to compensate the influence of the communication delays among the power devices in MGs or between the devices and upper level control, and reduce data loss [110][111][112][113]. When the control systems are decoupled, the characteristic equation of secondary control can be described as [192]:…”
Section: Random Communication Delaymentioning
confidence: 99%
“…An arc from node j to node i is denoted by ( , ), where node j receives information from node i. aij is the weight of the arc connecting vi to vj. The multiagent consensus algorithms implemented across the MG system converge over time according to [29]. The global system dynamics can therefore be given as (15) and (16).…”
Section: Communication Networkmentioning
confidence: 99%
“…It has been demonstrated that the hierarchical control scheme can effectively restore the PCC voltage deviation. However, accurate PCC voltage control relies heavily on effective communication [24], which increases the system cost and reduce the operational reliability.…”
Section: Introductionmentioning
confidence: 99%